Promoting local food systems through public procurement in the European Union - Muñoz Gómez, Marta J. (Przegląd Prawa Rolnego, 2023)
An attempt is made in this article to determine the possible role of strategic public procurement in the promotion of local food systems. The question asked is whether the principles of competition law that regulates the EU’s single market, fully applied in the framework of public procurement, stand in confrontation with the promotion of local food systems. It has been shown that local food systems can be a valid strategical clause included in public procurement procedures, as they enhance various social and environmental general interests that provide consumer’s welfare by improving competition. The local food clause should be defined in the public procurement procedures without reference to a specific administrative territory, whether national or regional and be proportional and suitable to secure the attainment of the general interests’ objectives.